2020
DOI: 10.1186/s12944-019-1167-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flaxseed oil rich in omega-3 suppresses severity of type 2 diabetes mellitus via anti-inflammation and modulating gut microbiota in rats

Abstract: Background: Type 2 diabetes mellitus (T2DM) is closely associated with hyperglycemia, abnormal lipid profiles, chronic low-grade inflammation and gut dysbiosis. Dietary intervention plays a crucial role in the control of diabetes. Flaxseed oil (FO), a plant-derived omega-3 (ω-3) polyunsaturated fatty acids (PUFAs), is rich in α-linolenic acid (ALA) which has been proved to benefit for chronic metabolic disease. However, the exact effects of dietary FO on T2DM remains largely unclear.Methods: In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 52 publications
6
94
0
6
Order By: Relevance
“…A previous report illustrated that omega-3 PUFAs and vitamin E co-supplementation down-regulated IL-8 and TNF-α expression in PCOS patients ( 71 ). Dietary ALA-rich FO inhibited the production of TNF-α, IL-1β, and IL-6 in T2DM and ALD ( 37 , 38 ). EPA treatment can decrease IL-1β and TNF-α but increase IL-10 in PCOS ( 27 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous report illustrated that omega-3 PUFAs and vitamin E co-supplementation down-regulated IL-8 and TNF-α expression in PCOS patients ( 71 ). Dietary ALA-rich FO inhibited the production of TNF-α, IL-1β, and IL-6 in T2DM and ALD ( 37 , 38 ). EPA treatment can decrease IL-1β and TNF-α but increase IL-10 in PCOS ( 27 ).…”
Section: Discussionmentioning
confidence: 95%
“…Flaxseed oil (FO), which is obtained from the seeds of flax plant, serves as mainly plant-derived omega-3 PUFAs [α-linolenic acid (ALA, 18:3 omega-3)] sourced to non-fish eaters. Dietary FO supplementation possesses the ability to attenuate chronic metabolic diseases ( 37 , 38 ). Furthermore, FO was previously reported to enhance the insulin level, lower the blood glucose level, and restore the enzymatic antioxidant barrier in diabetic rats by blocking insulin resistance ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the abundance of Fimicutes was decreased after irradiation, and those of Bacteroidetes and Actinobacteria were increased after PC intervention. A previous study found that Fimutes abundance was inversely related to the levels of various inflammatory factors, while Bacteroidetes was just the opposite [ 50 ]. This shows that the inflammation level of lung tissue is closely related to the flora of the lungs and even the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In a diabetic rat model study [ 62 ], the administration of flaxseed oil (rich in α-linoleic acid) seems to improve glucose metabolism, reduce interleukin 1-β, TNF-α and malondialdehyde, compared to the control group. In particular, the analytical sequencing of the intestinal microbiota showed a reduction of Firmicutes and Blautia that positively correlate with inflammatory cytokines such as interleukin-1β, TNF-α, LPS, etc.…”
Section: Mediterranean Diet and Microbiota Compositionmentioning
confidence: 99%